Perbedaan Model Problem Based Learning Berbantuan Media Audio Visual Terhadap Kemampuan Kognitif SDN Kaligawe Semarang - Maftukah, Maftukah; Kartinah, Kartinah; Adi, Retno Wulandari; Suyoto, Suyoto (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to determine the difference in applying the Problem Based Learning model assisted by audio-visual media to the cognitive abilities of students at SDN Kaligawe Semarang. The method used is a quantitative method of the pre-experimental type with a one-group pretest-posttest design. The population of this study was all students of class VB at SDN Kaligawe for the 2023/2024 academic year, totaling 27 students with 11 male students and 16 female students. The data collection technique was through a cognitive learning outcome test. The average pretest score was 64.07, while the average posttest score was 85.00. Based on the results of the hypothesis test, the pretest and posttest data yielded a value of 0.000 ≤ 0.05. Then, the average N-gain value of cognitive learning outcomes was 0.6031 with moderate criteria.